2006
DOI: 10.1124/jpet.105.097139
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Linkage of Apolipoprotein E to Albumin Nanoparticles Strongly Enhances Drug Transport into the Brain

Abstract: Drug delivery to the brain is becoming more and more important but is severely restricted by the blood-brain barrier. Nanoparticles coated with polysorbates have previously been shown to enable the transport of several drugs across the blood-brain barrier, which under normal circumstances is impermeable to these compounds. Apolipoprotein E was suggested to mediate this drug transport across the blood-brain barrier. In the present study, apolipoprotein E was coupled by chemical methods to nanoparticles made of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(191 citation statements)
references
References 39 publications
3
185
0
3
Order By: Relevance
“…The values of regional blood volumes used to correct brain radio activities were in accordance with those published previously [16,17]. Mice brains were divided into three regions, the two hemispheres and the cerebellum.…”
Section: Brain Distribution Studiesmentioning
confidence: 82%
“…The values of regional blood volumes used to correct brain radio activities were in accordance with those published previously [16,17]. Mice brains were divided into three regions, the two hemispheres and the cerebellum.…”
Section: Brain Distribution Studiesmentioning
confidence: 82%
“…140 The reason for such interaction is concluded to be due to the absorption of endogenic LDL from the plasma by polysorbate 80 and in the interaction with the brain endotheliocytes in accordance with the Trojan horse principle. The role of apoE has been demonstrated in work by Michaelis et al in 2006. 141 Two types of albumin nanoparticles coated with polysorbate 80 and particles with covalently bound apoE on their surface exhibited approximately equal ability to transport MD through the BBB.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…The duration of drug action attained with the bifunctional PLGA nanoparticles was longer than that attained using other nanoparticulate systems. 107,108 Biodistribution studies of the bifunctional PLGA nanoparticles revealed that 6% of the total injected dose of loperamide was localized inside the brain parenchyma of rats. This phenomenon could be attributed to interactions between the bifunctional PLGA nanoparticles and sialic acid receptors in the brain.…”
Section: Sialic Acid-functional Plga Nanoparticlesmentioning
confidence: 99%